ANALYTICAL STUDY ON BEHAVIOUR AND PERFORMANCE OF INFILLED FRAME STRUCTURE WITH REINFORCED ECCENTRIC OPENING - Wirawan, I Putu Agus Putra; Wiryadi, I Gede Gegiranang; Tubuh, I Ketut Diartama Kubon; Pradnyadari, Ni Luh Made Ayu Mirayani (Journal of Applied Engineering Science, 2023)
This numerical analysis has discussed the behaviour of the frame structure with eccentric infill wall opening modelled with shell and strut elements. In the beginning, validation models were created by following the laboratory tests results. Then, a simple one-storey infill frame structure with an opening was modelled with varying ratios by taking the strut angle formed to obtain an equation for the strut width that corresponds to the behaviour of shell element model with strut angles variation. The strut width equation was then applied to the 3-storey infill frame structures. The behaviour comparison between the strut and shell element model was then investigated by linear and nonlinear static analysis. The strut width equation for infill wall frame with eccentric openings (Weo) is determined by modifying the stiffness coefficient (Ce) based on the opening ratio. The application of the Weo equation to the infill frame model showed that the strut model had a comparable behaviour to the shell element model. The drift ratio comparison showed that the smaller the strut angle, the greater the structure stiffness. The pushover analysis shows the infilled frame model was able to withstand a larger base shear force than the open frame model.